Zero-Touch Slicing: Revolutionizing 5G Network Management through AI and Automation - Saikat Choudhury, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Zero-Touch Slicing represents a revolutionary approach in modern telecommunications networks, particularly in 5G and future 6G systems, leveraging artificial intelligence and machine learning for automated network management. This comprehensive article explores the fundamental architecture, implementation strategies, and real-world applications of Zero-Touch Slicing. The article examines how AI-driven automation transforms traditional network management through predictive analytics, automated decision-making, and closed-loop optimization. It evaluates the technology's impact across enterprise environments, smart city infrastructures, and dynamic service provisioning scenarios. The article demonstrates significant improvements in operational efficiency, service quality, and business agility through automated network slice management. Furthermore, it analyzes the future implications and benefits of this technology, highlighting its potential to revolutionize network operations in the evolving telecommunications landscape.
Keywords: Network Slicing; Artificial Intelligence; Network Automation; Machine Learning; 5G Networks